Transition‐Metal Dichalcogenide NiTe2: An Ambient‐Stable Material for Catalysis and Nanoelectronics. (29th March 2020) - Nappini, Silvia; Boukhvalov, Danil W.; D'Olimpio, Gianluca; Zhang, Libo; Ghosh, Barun; Kuo, Chia‐Nung; Zhu, Haoshan; Cheng, Jia; Nardone, Michele; Ottaviano, Luca; Mondal, Debashis; Edla, Raju; et al.
Abstract: By means of theory and experiments, the application capability of nickel ditelluride (NiTe2 ) transition‐metal dichalcogenide in catalysis and nanoelectronics is assessed. The Te surface termination forms a TeO2 skin in an oxygen environment. In ambient atmosphere, passivation is achieved in less than 30 min with the TeO2 skin having a thickness of about 7 Å. NiTe2 shows outstanding tolerance to CO exposure and stability in water environment, with subsequent good performance in both hydrogen and oxygen evolution reactions. NiTe2 ‐based devices consistently demonstrate superb ambient stability over a timescale as long as one month. Specifically, NiTe2 has been implemented in a device that exhibits both superior performance and environmental stability at frequencies above 40 GHz, with possible applications as a receiver beyond the cutoff frequency of a nanotransistor. Abstract : NiTe2 is an ambient‐stable transition‐metal dichalcogenide suitable for electrocatalysis and nanoelectronics. NiTe2 ‐based electrodes show outstanding tolerance to CO poisoning and stability in a water environment, with good performance in both hydrogen and oxygen evolution reactions. When exposed to the atmosphere, the NiTe2 surface is passivated with a sub‐nanometric TeO2 skin in a few minutes. Implemented microwave receivers are stable and particularly efficient.